2016
DOI: 10.1111/jfbc.12324
|View full text |Cite
|
Sign up to set email alerts
|

γ-amino butyric acid-enriched barley bran lowers adrenocorticotropic hormone and corticosterone levels in immobilized stressed rats

Abstract: This work aims to evaluate the potential effects of γ‐amino butyric acid (GABA)‐fortified barley bran against chronic stress induced Sprague‐Dawley rats. Animals were divided into four groups (n = 6), based on diet; control group (C), stress with no treatment (STR + NT), stress plus dietary Panax ginseng at 100 mg/kg (positive control group, STR + PG), and stress plus 0.5% GABA‐fortified barley bran (STR + BB‐G). After 21 days, stress biomarkers and liver toxicity biomarkers were measured. The stress biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Interestingly, the in ovo feeding of GABA could reduce the plasma corticosterone levels of the birds exposed to HS. Earlier studies have revealed that dietary and GABAenriched barley bran could lower adrenocorticotropic hormone (ACTH) and corticosterone levels in pigs and rats [46,47]. Indeed, under stressful conditions, the hypothalamus releases the corticotropin-releasing hormone, which stimulates the secretion of ACTH from the anterior pituitary gland [48].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the in ovo feeding of GABA could reduce the plasma corticosterone levels of the birds exposed to HS. Earlier studies have revealed that dietary and GABAenriched barley bran could lower adrenocorticotropic hormone (ACTH) and corticosterone levels in pigs and rats [46,47]. Indeed, under stressful conditions, the hypothalamus releases the corticotropin-releasing hormone, which stimulates the secretion of ACTH from the anterior pituitary gland [48].…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative diseases including AD, Parkinson's disease, and Huntington's disease have threatened human health and the quality of life in elderly people (Ross & Poirier, ). Advancement of industrialization (Vijaya Abinaya et al, ), lack of physical exercise, and Western diets trigger oxidative stress, which acts as a major risk factor for cognitive dysfunction and dementia in the elderly (Hillman, Erickson, & Kramer, ). Phytonutrients play a major role in the prevention of dementia (Kalaria et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…TG and TC from liver tissue were analyzed using a previously described method (Vijaya Abinaya et al., ). Tissue was homogenized using chloroform: methanol solution (2:1) was vortexed and centrifuged.…”
Section: Methodsmentioning
confidence: 99%